A quasi-experimental trial on effectiveness of health education module (IPVP) on intimate partner violence prevention among girls at shelter homes: a study protocol - Jafri, Faridah; Kadir @ Shahar, Hayati; K.C. Mani, Kulanthayan; Tan, Kit Aun (Elsevier, 2021)
Background: Intimate partner violence (IPV) is among major public health concerns and a violation of human rights. The global lifetime prevalence of physical and/or sexual IPV among all ever-partnered women was 30%. Statistics in Malaysia demonstrate that IPV constitutes the most common form of violence against women with a doubled number of reported cases in 10 years (from 2006 to 2016). Adolescents and young adults, particularly those exposed to prior abuse, are at high risk of experiencing IPV and will significantly benefit from early intervention programs. Objective: The study aims to develop, implement and evaluate the effectiveness of health education module on knowledge and attitude on IPV, conflict resolution skills and the likelihood of help-seeking behaviour among girls at shelter homes. Method: A quasi-experimental pilot study will be conducted which involved six children's shelter homes in six states across Malaysia. Randomly selected respondents who fulfilled the inclusion criteria will be invited to participate in the study. Health education module based on Information-Motivation-Behaviour Theory will be delivered via recorded health talks and videos coordinated by liaison officers. Data at three-time points at baseline, immediate and three months post-intervention will be collected via a self-administered online survey. A validated questionnaire will be used to assess patients' demographic details, history of prior abuse, knowledge and attitude on IPV, conflict resolution skills and the likelihood of help-seeking behaviour. Descriptive and inferential statistics will be applied for data analysis using IBM Statistical Package for Social Sciences version 25. Longitudinal correlated data on knowledge and attitude on IPV, conflict resolution skills and the likelihood of help-seeking behaviour at pre-intervention, immediate post and three months post-intervention will be analysed using Generalized Linear Mixed Model (GLMM). Outcome: It is expected that knowledge and attitude on IPV, conflict resolution skills and likelihood of help seeking behaviour score is greater in intervention group than control group, indicating the effectiveness of the health education module, IPVP.